MO1022CENTRAL VENOUS CATHETERS FIRST - THE ACHILLES' HEEL IN PEDIATRIC HEMODIALYSIS VASCULAR ACCESS. (29th May 2021) - Domingos, Ana; Teixeira, Ana; Matos, Paula; Rocha, Liliana; Almeida, Paulo; Costa, Teresa; Faria, Maria do Sameiro; Mota, Maria Conceição
Abstract: Background and Aims: Management of children with end-stage kidney disease (ESKD) requiring dialysis is always challenging and particular concerns exists regarding vascular access. International reports through the years are not satisfactory, with a high rate of central venous catheter (CVC), when "Fistula First" is the goal in Hemodialysis (HD). Suggested reasons for this phenomenon include, for example, age-related anatomical limitations, shorter awaiting times for or "scheduled" transplantation, pain and anxiety related to punctures or lack of pediatric/surgical expertise. Here we present the results of the last 13 years of experience in pediatric HD vascular access from a reference center in northern Portugal. Method: A retrospective descriptive study of patients admitted to our pediatric HD Unit between January 2007 and December 2020. Clinical data was collected from medical records. Results: 40 patients were enrolled, mainly boys (n=22, 55%), mean age at admission 10.9±5.3 years (1-17 years), 63% weighing more than 30 kg (n =25) and 15% less than 15kg (n=6). More than half were incident patients starting on HD (n=22, 55%), 42.5% were transferred from peritoneal dialysis (PD) and one patient had a previous kidney transplant (KT). Regarding CKD etiology, 52.5% (n=21) were mainly due to congenital anomalies of the kidney and urinary tract; chronic glomerulonephritis was responsible for 20% of cases (n=8). Most patients initiated HD with a CVC (n=35, 87.5%), including two patients with an arteriovenous fistula (AVF) who required a temporary CVC until fistula maturation. At the end of follow-up, about 45% of the patients ended up with an AVF (comparing to 17.5% at the beginning) and, not unexpectedly, 88.9% (n=16) of them weighed more than 30kg and only one child less than 15 kg. The mean duration of dialysis was 1.2±1.8 years (1 month-8 years); 24 patients were submitted to KT (60%), 6 transferred to PD (15%) and only 4 remain on HD. Average waiting times for KT are quite longer in patients with AFV (1.7±2 years), in comparison to CVC (0.4±0.3 years). Conclusion: CVC is by far the most used access in incident patients starting on HD. In our center it seems justified by the anatomical limitations of younger and smaller patients, as wells as expected shorter awaiting time for KT. Infectious and mechanical complications must be weighed when using CVC, mainly considering the probable need for different renal replacing techniques over the years. Although our data is quite similar to several international reports and other center experiences, we still aim for the best, with an expected improvement of these results within the coming years. For now, a notable increase in AVF placement at the end of the follow-up is already an encouraging fact.